Design of a Wide Dual-Band Coplanar Probe Feed Antenna for WLANs Applications - Abdulhussein, Nabil Eyad; Abdullah, Abdulkareem S. (Iraqi Journal for Electrical and Electronic Engineering, 2020)
This paper presents a new design to obtain wide dual-band operation from a coplanar probe feed antenna loaded with two shorted walls. The lower band of proposed antenna has a 10 dB bandwidth of 611 MHz (24.18%) around the center frequency 2527MHz, and the upper band has a bandwidth of 1255 MHz (27.88%) around the center frequency 4501MHz. The obtained bandwidths cover WLANs operations on all bands. The bandwidth of the first operating frequency covers ISM band (2400- 2483.5) MHz, which is required by IEEE 802.11b, g and Bluetooth standards, and the bandwidth of the second operating frequency covers U-NII1 (5150-5350) MHz band, which is required by IEEE 802.11a and HiperLAN2 standards, and also covers U-NII2 (5470-5725) MHz and U-NII3/ISM (5725-5825) MHz bands, which are required by IEEE 802.11a standard. A three dimensional finite-difference time-domain (3-D FDTD) method is employed to analyze the proposed structure and find its performance. The simulated results are compared with the experimental results.